Prediction of significant coronary lesions by SPECT myocardial perfusion. Results from a national reference hospital in Lima-Peru - Talledo-Paredes, Luisa S. (2022)
Objective. To determine the discriminative capacity of myocardial perfusion with single photon emission tomography (SPECT) to predict coronary obstructions by coronary angiography. To determine mortality and major cardiovascular events at follow-up. Materials and methods. Retrospective observational study with clinical follow-up in patients undergoing SPECT and then coronary angiography. We excluded patients with myocardial infarction and percutaneous and/or surgical revascularization in the previous 6 months. Results: 105 cases were included in the study. The most commonly used SPECT protocol was pharmacological (70%). Patients with perfusion defect ≥10% of total ventricular mass (TVM) had significant coronary lesions (SCL) in 88% of cases (sensitivity 87.5% and specificity 83%). On the other hand, having ischemia ≥10% of the TVM was associated with 80% SCL (sensitivity: 72%, specificity: 65%). Clinical follow-up at 48 months evidenced that a perfusion defect ≥ 10% was predictive of major cardiovascular events (MACE) in both univariate (HR=5.3; 95%CI 1.2 - 22.2; p=0.022) and multivariate (HR= 6.1; 95%CI 1.3 - 26.9; p= 0.017) analyses. Conclusions. Having a perfusion defect ≥10% of the MVT in the SPECT study predicted with high probability and sensitivity the existence ofSCL (>80%); moreover, this group had higher MACE at follow-up.